Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 4, Quốc hội khóa XV (Số: 374/BC-UBTVQH15) - UBTVQH (2022)
Toàn văn Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 4, Quốc hội khóa XV (Số: 374/BC-UBTVQH15)